A method for obtaining a reliable joint between IN718 nickel-based alloy and 316LN steel by transient liquid phase diffusion bonding
By using nickel-based alloy foil as the intermediate layer between IN718 nickel-based alloy and 316LN steel and using instantaneous liquid phase diffusion connection technology, the cracking and thermally affected zone problems during welding are solved, and high-strength, uniformly structured joints are achieved, and the pressure and deformation required by the process are reduced.
Patent Information
- Application Number
- CN202111423077.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-26
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-11-26
AI Technical Summary
The prior art has problems such as solidification cracking, microcracking, and precipitation of niobium-rich phase in the heat-affected zone when welding IN718 nickel-based alloy and 316LN steel, and the diffusion connection process requires high pressure and high temperature, which limits its applicability.
Ni-Cr-Fe-Si-B is used as the intermediate layer, and the instantaneous liquid phase diffusion connection technology is used to heat up to 1000-1100℃ under vacuum at a temperature increase rate of 5-10℃/min, and the insulation is carried out for 15-60 minutes, and a pressure of 0.5-1MPa is applied during the process.
The obtained joint structure and composition are uniformly consistent with the base material, the mechanical properties of the joint are similar to that of the base material, the room temperature shear strength reaches 225-260MPa, the tensile strength reaches 400-550MPa, and the pressure required for the connection is small, and the workpiece deformation is small.
Smart Images

Figure CN116174883B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to a metal material welding technology, and more specifically, relates to a method for obtaining an instantaneous liquid phase diffusion connection of a reliable joint of IN718 nickel-based alloy and 316LN steel. Background Art
[0002] With the development of industrial technology, the instantaneous liquid phase joining of dissimilar metals has attracted great attention. In fact, in the fields of energy, nuclear industry, aerospace, etc., metals with different structures and properties need to be connected to each other to manufacture better products. Coupling multiple properties of interest in a single structure is also a hot topic in the current research on dissimilar metal joining. At the same time, the joining of dissimilar alloys is also considered a cost-reducing technology for repairing damaged parts.
[0003] Bimetallic joints of nickel-based superalloy IN718 and AISI 316LN austenitic stainless steel are currently used in the aerospace industry and nuclear power plants. This is due to their excellent mechanical properties, oxidation resistance at room and elevated temperatures, and corrosion resistance. However, solidification cracking, microcracks, and precipitation of niobium-rich phases in the heat-affected zone are common problems in IN718 parts during welding. On the other hand, although austenitic stainless steels exhibit higher weldability compared to other stainless steels, their high expansion coefficient and low thermal conductivity may lead to deformation and residual stresses in the welded joints of these steels. One of the problems with welding is the lack of sufficient mechanical and corrosion resistance to ensure reliable applications. The main reason for these welding problems is the formation of hard and brittle eutectic structures in the weld layer. These components are formed during non-isothermal solidification and are the preferred location for cracking due to their low plasticity and toughness. In addition, diffusion bonding is another technology that has been widely used in recent decades to join various types of advanced alloys. However, the application of high pressure and temperature during diffusion welding and the basic need for high-quality surface treatment of samples limit its applicability.
[0004] Transient liquid phase diffusion bonding (TLP) combines the advantages of solid phase diffusion bonding and brazing. An intermediate layer containing melting-reducing elements is added during the connection process. The pressure required for connection is very small, so the residual stress and deformation of the joint are small. The joint structure and composition obtained by transient liquid phase diffusion bonding technology are uniform and consistent with the parent material, and the mechanical properties of the joint are also similar to those of the parent material. At present, transient liquid phase diffusion bonding technology has been widely used in the welding field of high-temperature alloys, ceramics, heat-resistant steel and other materials.
[0005] The transient liquid phase joining (TLP) process is a new process invented in the 1980s, which combines the advantages of diffusion welding and welding processes. In the transient liquid phase joining process, a low-melting-point amorphous foil with a melting-reducing (MPD) element is used between two pieces of base materials. The diffusion of the MPD element from the liquid intermediate layer to the base material occurs within a certain holding time at the joining temperature, which leads to isothermal solidification. Therefore, the TLP method can produce welded joints with excellent performance, no interface, and no intermediate layer residue. At present, TLP welding has become the preferred welding method for various advanced materials, such as advanced ceramics, composite materials, various heat-resistant / corrosion-resistant alloys, and single crystal alloys. At the same time, the TLP welding process also has great application potential in traditional structural materials such as carbon steel and alloy steel. Summary of the invention
[0006] The technical purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for obtaining a reliable joint of IN718 nickel-based alloy and 316LN steel by instantaneous liquid phase diffusion bonding, utilizing an alloy foil intermediate layer and designing a thermal cycle process for instantaneous liquid phase diffusion bonding, thereby obtaining a reliable joint of IN718 nickel-based alloy and 316LN steel with uniform structure and good mechanical properties.
[0007] The technical purpose of the present invention is achieved through the following technical solutions.
[0008] A method for instantaneous liquid phase diffusion bonding of a reliable joint of IN718 nickel-based alloy and 316LN steel is provided, wherein a nickel-based alloy foil Ni-Cr-Fe-Si-B is arranged between the IN718 nickel-based alloy and the 316LN steel, the temperature is raised from room temperature to 1000-1100°C at a heating rate of 5-10°C / min under vacuum conditions, the temperature is kept at that temperature for 15-60 minutes, the temperature is cooled to room temperature with the furnace, and during this process, a pressure of 0.5-1MPa is applied in a direction perpendicular to the surfaces to be connected.
[0009] The chemical composition of the IN718 nickel-based alloy is Ni 53.67wt.%, Cr 19.35wt.%, Co0.007wt.%, Al 0.36wt.%, Mo 3.00wt.%, Mn 0.02wt.%, Si 0.08wt.%, Nb 5.43wt.%, and the rest is Fe element; the chemical composition of the 316LN steel is Ni 12.85wt.%, Cr 16.61wt.%, Co0.011wt.%, Al 0.009wt.%, Mo 2.10wt.%, V 0.003wt.%, Mn 1.68wt.%, Si 0.52wt.%, Nb 0.007wt.%, and the rest is Fe element; the chemical composition of the nickel-based alloy foil Ni-Cr-Fe-Si-B is Cr 7wt.%, Si4.5wt.%, B 3wt.%, Fe 3wt.%, and the rest is Ni element.
[0010] Before diffusion bonding, IN718 nickel-based alloy and 316LN steel samples were pretreated as follows: block samples with a size of 30 mm × 15 mm × 10 mm were cut from IN718 and AISI 316LN samples using a wire cutting machine. 2 ) were mechanically ground with 150#-1200# sandpaper in turn, and then ultrasonically cleaned with acetone for 15 min and alcohol for 15 min.
[0011] Before diffusion bonding, the nickel-based alloy foil Ni-Cr-Fe-Si-B was pretreated as follows: both sides of the foil were polished to 1200# with sandpaper; ultrasonically cleaned in acetone for 15 minutes and dried; and ultrasonically cleaned in alcohol for 15 minutes and dried.
[0012] During diffusion bonding, transient liquid phase diffusion bonding is carried out in a vacuum diffusion welding furnace.
[0013] During diffusion bonding, the room temperature is 20-25°C.
[0014] During diffusion bonding, the vacuum degree is 1-5×10 -3 Pa.
[0015] During diffusion bonding, a pressure of 0.75 MPa is applied perpendicularly to the surfaces to be bonded.
[0016] During diffusion bonding, the insulation temperature is selected to be 50-80°C higher than the melting temperature of the nickel-based alloy foil Ni-Cr-Fe-Si-B, preferably 1050°C.
[0017] During diffusion bonding, the heating rate is 5-8°C / min and the cooling rate is 5-30°C / min.
[0018] After diffusion bonding, intermetallic compound Ni appears in the diffusion bonding area. 23 B6, CrB, Ni3Si and Ni-Si-B precipitates.
[0019] The connection method of the present invention uses Ni-Cr-Fe-Si-B amorphous foil to perform instantaneous liquid phase diffusion connection on IN718 nickel-based alloy and 316LN steel samples. The pressure required for connection is small, the connection time is short, the deformation of the workpiece is small, the obtained joint structure and composition are uniform and consistent with the parent material, the mechanical properties of the joint are also similar to those of the parent material, the room temperature shear strength reaches 225-260MPa, and the tensile strength reaches 400-550MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope image of the instantaneous liquid phase diffusion bonding joint of IN718 nickel-based alloy and 316LN steel after being kept at 1050℃ for 15 minutes.
[0021] Figure 2 This is a scanning electron microscope image of the instantaneous liquid phase diffusion bonding joint of IN718 nickel-based alloy and 316LN steel after being kept at 1050℃ for 45 minutes.
[0022] Figure 3 This is a scanning electron microscope image of the instantaneous liquid phase diffusion bonding joint of IN718 nickel-based alloy and 316LN steel after being kept at 1050℃ for 60 minutes.
[0023] Figure 4 These are the microstructural images of the instantaneous liquid phase diffusion bonding joint of IN718 nickel-based alloy and 316LN steel at a bonding temperature of 1050°C and a holding time of 15 min, where a and c are secondary electron images, and b and d are backscattered electron images.
[0024] Figure 5 yes Figure 4 High magnification SEM photo of Ni3Si.
[0025] Figure 6 These are the microstructure photos and EDS surface scan photos of the ASZ precipitates in Example 1 of the present invention.
[0026] Figure 7 TEM image of CrB phase and the corresponding electron diffraction pattern
[0027] Figure 8 Ni3Si and Ni 23 TEM image of B6 phase and the corresponding electron diffraction pattern.
[0028] Fig. 9 It's Ni 23TEM image of B6 phase and the corresponding electron diffraction pattern.
[0029] Fig.10 It is the hardness distribution diagram of the joint area of IN718 nickel-based alloy and 316LN steel samples connected at a connection temperature of 1050℃ for 15, 45, and 60 minutes. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described below in conjunction with specific embodiments. IN718 nickel-based alloy and 316LN steel were purchased from Guizhou Aerospace Xinli Technology Co., Ltd., and nickel-based alloy foil Ni-Cr-Fe-Si-B was produced by Zhengzhou Jinou Welding Co., Ltd. using a high-speed strip-spinning method based on the elements and their contents designed by the research team.
[0031] Example 1
[0032] Step 1: Use wire cutting machine to cut block samples with size of 30mm×15mm×10mm from IN718 and AISI 316LN samples. Before connecting, 2 ) are mechanically ground with 150#-1200# sandpaper in sequence.
[0033] Step 2: Cut the Ni-Cr-Fe-Si-B amorphous foil into 30×15mm 2 Use sandpaper to sand both sides of the foil to 1200#.
[0034] Step 3: Before connection, ultrasonically clean the sample and alloy foil in acetone for 15 minutes, dry them, and then ultrasonically clean them in alcohol for 15 minutes and dry them.
[0035] Step 4: Place the Ni-Cr-Fe-Si-B amorphous foil (i.e., nickel-based alloy foil Ni-Cr-Fe-Si-B) between the two samples, and place the assembled sample in a vacuum furnace to evacuate the vacuum. When the vacuum degree reaches 5×10 -3 Heating was started at 0.050°C at a heating rate of 5°C / min, and a pressure of 0.75MPa was applied and kept warm for 15min. The sample was then cooled to room temperature in the furnace to obtain a connected sample.
[0036] Example 2
[0037] Step 1: Use wire cutting machine to cut block samples with size of 30mm×15mm×10mm from IN718 and AISI 316LN samples. Before connecting, 2 ) are mechanically ground with 150#-1200# sandpaper in sequence.
[0038] Step 2: Cut the Ni-Cr-Fe-Si-B amorphous foil into 30×15mm 2 Use sandpaper to sand both sides of the foil to 1200#.
[0039] Step 3: Before connection, ultrasonically clean the sample and alloy foil in acetone for 15 minutes, dry them, and then ultrasonically clean them in alcohol for 15 minutes and dry them.
[0040] Step 4: Place the Ni-Cr-Fe-Si-B amorphous foil (i.e., nickel-based alloy foil Ni-Cr-Fe-Si-B) between the two samples, and place the assembled sample in a vacuum furnace to evacuate the vacuum. When the vacuum degree reaches 5×10 -3 Heating was started at 0.050°C at a heating rate of 5°C / min, and the temperature was raised to 1050°C. A pressure of 0.75MPa was applied and the temperature was kept at this temperature for 45min. The temperature was then cooled to room temperature along with the furnace to obtain a connected sample.
[0041] Example 3
[0042] Step 1: Use wire cutting machine to cut 30mm×15mm×
[0043] 10mm block specimen, before connecting the specimen (30×15mm 2 ) are mechanically ground with 150#-1200# sandpaper in sequence.
[0044] Step 2: Cut the Ni-Cr-Fe-Si-B amorphous foil into 30×15mm 2 Use sandpaper to sand both sides of the foil to 1200#.
[0045] Step 3: Before connection, ultrasonically clean the sample and alloy foil in acetone for 15 minutes, dry them, and then ultrasonically clean them in alcohol for 15 minutes and dry them.
[0046] Step 4: Place the Ni-Cr-Fe-Si-B amorphous foil (i.e., nickel-based alloy foil Ni-Cr-Fe-Si-B) between the two samples, and place the assembled sample in a vacuum furnace to evacuate the vacuum. When the vacuum degree reaches 5×10 -3 Heating was started at 0.050°C at a heating rate of 5°C / min, and the temperature was raised to 1050°C. A pressure of 0.75MPa was applied and the temperature was kept at this temperature for 60min. The temperature was then cooled to room temperature in the furnace to obtain a connected sample.
[0047] The microstructure of the connection sample prepared in the above embodiment was characterized. The weld of the sample was centered and cut into a 4 mm × 4 mm × 3 mm cuboid. The cross section of the sample perpendicular to the connection surface was mechanically ground to 3000 mm. #Sandpaper, and then polished according to standard procedures. The metallographic samples were etched with aqua regia (volume ratio HCL:HNO3=3:1). The microstructure was observed using a JSM-7800F scanning electron microscope (SEM), and the phase analysis was performed by energy dispersive spectrometer (EDS). The sample was further analyzed by a Tecnai G2 F30 field emission transmission electron microscope (TEM), and the structure of the second phase was characterized by selected area electron diffraction (Selected Area Electron Diffraction), and the micromorphology of the second phase and dislocation was observed. Since the width of the weld is only about 100μm and the position is not easy to determine, the preparation of the transmission sample requires the use of two methods: ion thinning and coating. A wire cutting machine was used to cut a 0.3mm thick slice perpendicular to the weld from the TLP connection joint of RAFM steel, and the weld was located in the center of the slice as much as possible. Then, grind the slices with 400#-2000# sandpaper. When the slice thickness is less than 50μm, use the weld as the diameter and punch the grinded sample slice into a 3mm diameter disc with a puncher, and then use the ion bombardment thinning equipment to thin the sample.
[0048] In order to evaluate the mechanical properties of TLP joints, the microhardness test of IN718 and 316LN TLP joint samples was carried out using NH-6L Vickers hardness tester to characterize the resistance to plastic deformation and strain hardening ability of the joints. Before the test, the surface of the sample was mechanically ground with different types of sandpaper and then polished with diamond polishing agent. During the test, a load of 25g was selected, and a test point was taken every 20μm from the center of the weld to the parent material. The regular tetrahedral diamond indenter was pressed into the surface of the sample. The loading time was 10s, and 3 points were tested at the same distance to take the average value. The room temperature tensile and shear tests of IN718 and 316LN TLP joint samples were carried out using CMT5105testing machine electronic universal material testing machine. Three samples were tested in each group of tests, and then the average value was taken. For details, please refer to the paper "Study on the microstructure formation and creep performance of transient liquid phase diffusion bonding joints of RAFM steel" of the research group.
[0049] As attached Figure 1—3 shows that the SEM photos of the instantaneous liquid phase diffusion bonding joints kept at 1050°C for different times using the technical solution of the present invention can achieve the connection of IN718 and 316LN. Test results of Example 1—the average shear strength of the joint is 228MPa, and the average tensile strength of the joint is 412MPa; Test results of Example 2—the average shear strength of the joint is 238MPa, and the average tensile strength of the joint is 491MPa; Test results of Example 3—the average shear strength of the joint is 251MPa, and the average tensile strength of the joint is 526MPa.
[0050] As attached Figure 4 As shown in the figure, the SEM microstructure of the joint connected at 1050℃ for 15min is taken as an example. Different microstructures can be distinguished in the weld area, represented by points A to E. The SEM energy spectrum analysis results of these points are summarized in the table below.
[0051] It can be seen that the E region is a single-phase region without any intermetallic compound phase.
[0052]
[0053] Point A is rich in nickel and chromium, and it is inferred that phase A is a chromium-rich boride. Phase C is rich in Ni and contains a small amount of Cr and Si, and it is inferred that it is Ni 23 B6. Point E has a higher Si concentration (13.22 at.%), which is higher than the solubility limit of Si in Ni at room temperature (8 at.%), as shown in Figure 5 As shown in the figure, this area is composed of fine blocky precipitates with a particle size of 50-450nm; considering the chemical composition of area E, it is inferred that Ni3Si intermetallic compounds are formed in this area. The Si content at point B is higher, and the color is darker than that at point C in the backscattered electron microscopy image, so Ni-Si-B precipitates are formed in this area.
[0054] The microstructure of ASZ precipitates was characterized by SEM and EDS scanning, as shown in the attached Figure 6 As shown in the figure, each metal element is distributed in the measured joint area, and the content of different phases formed in the joint area cannot be quantitatively measured by SEM / EDS analysis. In order to determine the intermetallic compound phase formed in the ASZ, a TEM experiment was carried out, as shown in the attached figure. Figure 7 —As shown in 9. Figure 7 , Figure 8 and Fig. 9 The experimental results of selected area electron diffraction of the connected sample after being kept at 1050℃ for 15min show that the intermetallic compounds formed in the ASZ are mainly composed of Ni 23B6, CrB and Ni3Si, which is basically consistent with the analysis results shown in the above table. In Examples 2 and 3 where the holding time is changed, the SEM characterization shows that the morphology is basically consistent with that of Example 1. The intermetallic compounds formed are basically consistent through the judgment of material composition, holding temperature and time.
[0055] The hardness distribution in the welding area is used as a criterion for the uniformity of the joint structure and mechanical properties. Fig.10 The hardness distribution of the joint area of the samples connected at 1050℃ for 15, 45, and 60min is given, with the ordinate being the hardness and the abscissa being the joint area, with the base material IN718 on one side and the base material 316LN on the other side. It can be found from the figure that for the samples at 1050℃ and holding time of 15, 45, and 60min, the hardness value increases as it moves from the base material to the DAZ, then decreases as it reaches the ISZ, and reaches the maximum hardness value when it reaches the ASZ. In this case, the DAZ hardness value on the IN718 side is the highest, while the hardness value of the AISI 316LN base material is the lowest. The reason for the higher hardness of the DAZ is that a large amount of boride precipitation phases are formed in these areas. Considering that the DAZ on the IN718 side contains more boride precipitates and precipitated elements such as Ti, Cr, Mo, and Nb, its hardness value is higher than that on the DAZ on the AISI 316LN side. By extending the holding time, the content of intermetallic compounds in the ASZ is gradually reduced, and no continuous network is formed. Therefore, the hardness value of the ASZ zone decreases significantly with the increase of the holding time, and the average hardness values reach 636HV, 466HV, and 433HV respectively. However, it is worth noting that the boride precipitates in the DAZ are distributed discontinuously. It can be seen that compared with the ASZ precipitates, the DAZ precipitates have less effect on the joint strength.
[0056] According to the content of the present invention, the process parameters can be adjusted to achieve effective connection of IN718 nickel-based alloy and 316LN steel. The above is an exemplary description of the present invention. It should be noted that any simple deformation, modification or other equivalent replacement that can be done by other technicians in this field without spending creative labor falls within the protection scope of the present invention without departing from the core of the present invention.
Claims
1. A method for obtaining a transient liquid phase diffusion connection of a reliable joint of IN718 nickel-based alloy and 316LN steel, characterized in that: A nickel-based alloy foil Ni-Cr-Fe-Si-B is placed between IN718 nickel-based alloy and 316LN steel. The temperature is raised from room temperature to 1000-1100°C at a heating rate of 5-10°C / min under vacuum conditions, and the temperature is kept for 15-60 minutes. The furnace is cooled to room temperature and a pressure of 0.5-1MPa is applied perpendicular to the surface to be connected. Intermetallic compound Ni 23 B6, CrB, Ni3Si and Ni-Si-B precipitates; The chemical composition of the IN718 nickel-based alloy is Ni 53.67wt.%, Cr 19.35wt.%, Co 0.007wt.%, Al0.36wt.%, Mo 3.00 wt.%, Mn 0.02wt.%, Si 0.08wt.%, Nb 5.43wt.%, and the rest is Fe element; the chemical composition of the 316LN steel is Ni 12.85wt.%, Cr 16.61wt.%, Co 0.011wt.%, Al 0.009wt.%, Mo2.10wt.%, V 0.003wt.%, Mn 1.68wt.%, Si 0.52wt.%, Nb 0.007 wt.%, and the rest is Fe element; the chemical composition of the nickel-based alloy foil Ni-Cr-Fe-Si-B is Cr 7wt.%, Si 4.5wt.%, B 3wt.%, Fe 3wt.%, and the rest is Ni element.
2. A method for obtaining a transient liquid phase diffusion connection of a reliable joint of IN718 nickel-based alloy and 316LN steel according to claim 1, characterized in that: During diffusion bonding, the vacuum degree is 1-5×10 -3 Pa.
3. The method for obtaining a transient liquid phase diffusion connection of a reliable joint of IN718 nickel-based alloy and 316LN steel according to claim 1, characterized in that: During diffusion bonding, transient liquid phase diffusion bonding is carried out in a vacuum diffusion welding furnace.
4. The method for obtaining a transient liquid phase diffusion connection of a reliable joint of IN718 nickel-based alloy and 316LN steel according to claim 1, characterized in that: During diffusion bonding, a pressure of 0.75 MPa is applied perpendicularly to the surfaces to be bonded.
5. The method for obtaining a transient liquid phase diffusion connection of a reliable joint of IN718 nickel-based alloy and 316LN steel according to claim 1, characterized in that: During diffusion bonding, the insulation temperature is selected to be 50-80° C. higher than the melting temperature of the nickel-based alloy foil Ni-Cr-Fe-Si-B.
6. The method for obtaining a transient liquid phase diffusion connection of a reliable joint of IN718 nickel-based alloy and 316LN steel according to claim 1, characterized in that: During diffusion bonding, the heating rate is 5-8°C / min and the cooling rate is 5-30°C / min.
7. The method for obtaining a transient liquid phase diffusion connection of a reliable joint of IN718 nickel-based alloy and 316LN steel according to claim 1, characterized in that: Before diffusion bonding, IN718 nickel-based alloy and 316LN steel specimens were pretreated as follows: block specimens with a size of 30 mm × 15 mm × 10 mm were cut from IN718 and AISI 316LN specimens using a wire cutting machine. 2 ) were mechanically ground with 150#-1200# sandpaper in turn, and then ultrasonically cleaned with acetone for 15 minutes and alcohol for 15 minutes.
8. The method for obtaining a transient liquid phase diffusion connection of a reliable joint of IN718 nickel-based alloy and 316LN steel according to claim 1, characterized in that: Before diffusion bonding, the nickel-based alloy foil Ni-Cr-Fe-Si-B was pretreated as follows: both sides of the foil were polished to 1200# with sandpaper; ultrasonically cleaned in acetone for 15 minutes and dried; and ultrasonically cleaned in alcohol for 15 minutes and dried.
Citation Information
Patent Citations
Application of raney nickel as slurry reactor to synthesize methane catalyst
CN102942971A
Acoustic-induced transient liquid phase diffusion bonding method based on eutectic reaction
CN106735833A